A Sociocultural Analysis of Teachers’ Belief Changes: A Case of Two Teach-Abroad EFL Teachers - Sahiruddin, Sahiruddin; Arifani, Yudhi; Anyanwu, Clinton Chidiebere; Suryanto, Jati (Universitas Muhammadiyah Sidoarjo, 2024)
This inquiry explores English foreign language (EFL) teacher beliefs in teach-abroad (TA) contexts under the umbrella of Vygotsky’s sociocultural theory (SCT) of mind. The previously available literature on teacher beliefs has relied mostly on quantitative survey research concerning belief as an inert variable; an internal representation of experience is resilient to evolve. Due to the prevalence of the theory of mind or cognitive orientation under the sociocultural theory, this case study aims to examine two TA EFL teachers’ belief changes in the new TA context and conceptualize the teachers’ beliefs from a sociocultural perspective. The participants involved EFL teachers (both pseudonyms): Ivan (male, aged 26) and Melanie (female, aged 24) attending different types of TA were recruited for this research. We collected the data through pre-and post-TA interviews and teaching journals with other triangulated methods like teaching autobiographies and recall experiences. The findings advocated that EFL teachers’ teaching beliefs continuously evolve according to their TA goals and experiences, and their belief changes involve a remediation process that leads to different teaching actions. Their internalized EFL teaching beliefs within meaningful environments influence the success of their TA teaching. HIGHLIGHTS: EFL teachers’ teaching beliefs continuously evolve according to their TA goals and experiences EFL teacher’s belief changes involve a remediation process that leads to different teaching actions Socio-cultural context of teaching and learning practice facilitates the perception of teachers’ teaching beliefs.